Current approaches to collective burials in the late European prehistory : proceedings of the XVII UISPP World Congress (1-7 September 2014, Burgos, Spain). - Tomé, Tiago; Díaz-Zorita Bonilla, Marta; Silva, Ana Maria; Cunha, Claudia; Boaventura, Rui (Archaeopress Publishing Ltd, 2017)
The articles in this volume provide examples of different approaches currently being developed on Prehistoric collective burials of southern Europe, mostly focusing on case studies, but also including contributions of a more methodological scope.